PENINGKATAN KEMAMPUAN KOMUNIKASI DAN DISPOSISI MATEMATIS SISWA MELALUI PEMBELAJARAN KOPERATIF TIPE JIGSAW DI SMP MUHAMMADIYAH KOTA PADANGSIDIMPUAN - Masdelima Azizah Sormin (Universitas Muhammadiyah Tapanuli Selatan, 2017)
This research aims to determine: (1) the improvement of mathematical communication skill and disposition of students who received jigsaw cooperative learning and conventional learning, (2) the interaction between learning model and prior knowledge of the mathematical communication skill and student disposition. The research conducted in SMP Muhamadiyah Padangsidimpuan city. The researchtype is quasi-experimental pre-test-post-test control group design. The population in this study was all eighth-grade students of SMP Muhamadiyah Padangsidimpuan city and sample was 30 students in class VII-3 as an experimental class and 30 students in class VII-1 as a control class. Sampling was carried out through purpose sampling technique. The research instrument used is a mathematical communication skill test, questionnaire, student disposition. The hypothesis testing in this study usedtwo way ANOVA. The results showed that (1) the improvement of mathematical communication skill who received jigsaw cooperative learning is higher than conventional learning. The average of communication skill improvementused jigsaw cooperative learning and conventional learning respectively 0.64 and 0.65, and the improvement of student disposition respectively 0.43 and 0.45. (2) There is interaction between learning and prior knowledge of mathematical communicatin skill and student disposition.